Scaffolding Technique in Response to the Improvement of Indonesian Language Functions Policies - Iga Shevy Margaretta; Zuliati Rohmah (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This study aimed to find out the effect of the scaffolding technique proposed by Vygotsky (1987) which was carried out through peer tutor activities in the BIPA program at one of the universities in Malang. This research is a case study conducted on one foreign learner who participated in a private BIPA program. Qualitative methods are used to elaborate discussions based on the results of research findings. The main focuses of this study were the influence of peer tutoring activities and social interaction on the development of Indonesian language skills of the BIPA learner. The results of the study stated that the scaffolding technique carried out through peer tutoring was very helpful for learners in understanding the Indonesian language quickly. In addition, the activities that were carried out flexibly and more relaxed made the learner not feel the pressure of learning. The process of social interaction that the learner experienced with the environment also had a significant effect on the understanding of the Indonesian language and culture. An interesting thing was also found from the social interaction between the BIPA learner and the native Indonesian which was the changing lifestyle and thinking experienced by the learner.